Transient thermo-hydraulics and performance characteristics of single-phase natural circulation loop using hybrid nanofluids. (January 2020) - Sahu, Mayaram; Sarkar, Jahar; Chandra, Laltu
Abstract: Transient analysis of vertical heating and horizontal cooling rectangular single-phase natural circulation loop with various water-based hybrid nanofluids (Al2 O3  + Ag, Al2 O3  + Cu, Al2 O3  + TiO2, Al2 O3  + CNT, Al2 O3  + Graphene) with 1% volumetric concentration is studied numerically. Temporal fluctuation and time required to attain the steady-state, transient mass flow rate and energy-exergy performance parameters (effectiveness and total entropy generation) using hybrid nanofluids are compared with water. The effect of power input and geometry parameter (diameter and height) of the loop on transient performances is studied as well. The result reveals that the fluctuation of mass flow rate and time required to attain the steady-state are less for hybrid nanofluids as compared to water. However, platelet and cylindrical shaped nanoparticles yield a lower stability as compared to spherical shaped. The mass flow rate is enhanced with hybrid nanofluids, except Al2 O3  + CNT and Al2 O3  + Graphene, as compared to water. The energy-exergy performance of hybrid nanofluids is higher than water. The maximum increment in mass flow rate is shown by Al2 O3  + Ag hybrid nanofluid (3%), whereas Al2 O3  + Graphene shows the highest increment in effectiveness (25.4%) and highest decrement in total entropy generation (14.3%) as compared to water. Smaller diameter and lower height of loop are found preferable for the flow stability.